Teacher’s Perception of Personality Competence: “Is it Really Important?” - Rita Tri Ananda; Khoiriyah Khoiriyah; Asti Bhawika Adwitiya (Universitas Pendidikan Indonesia, 2024)
Ideally, teachers possess four competencies: professional, pedagogical, social, and personality. One of the competencies that did not get much attention is personality competency. This research employed a qualitative method with a phenomenological approach to understanding the teachers’ experiences and how they value and implement personality competence in their daily teaching practices. Interviews and observations of the teacher and headmaster inside and outside the class were conducted to obtain the data. The result suggested that the teachers have implemented it in their daily lives as teachers, despite having a limited understanding of the complex terminology in the concept of personality competency.